กระบวนการพัฒนาต้นแบบครูพี่เลี้ยงของนิสิตฝึกประสบการณ์วิชาชีพครู - เขียววิจิตร ชีวัน; แย้มรุ่ง รุ่งทิวา; เกษมเนตร ลัดดาวัลย์ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ งานวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ศึกษาองค์ประกอบการพัฒนาต้นแบบครูพี่เลี้ยงของนิสิตฝึกประสบการณ์วิชาชีพครูในโรงเรียนสาธิตมหาวิทยาลัยศรีนครินทรวิโรฒ ปทุมวัน 2) เพื่อพัฒนากระบวนการพัฒนาต้นแบบครูพี่เลี้ยงของนิสิตฝึกประสบการณ์วิชาชีพครูด้านการจัดการเรียนรู้ตามแนวการพัฒนาบทเรียนร่วมกัน เพื่อเตรียมความพร้อมครูพี่เลี้ยงให้มีสมรรถนะด้านความรู้และทักษะที่เหมาะสมเพื่อส่งเสริมความเป็นมืออาชีพ และเพื่อสร้างเครือข่ายชุมชนการเรียนรู้ทางวิชาชีพ (Professional Learning Community: PLC) การดำเนินงานวิจัยแบ่งเป็น 2 ระยะ ได้แก่ ระยะที่ 1 ร่างองค์ประกอบของต้นแบบครูพี่เลี้ยง และระยะที่ 2 ออกแบบกระบวนการพัฒนาต้นแบบครูพี่เลี้ยง เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบประเมินตนเองของครูพี่เลี้ยงด้านสมรรถนะการจัดการเรียนรู้และการนิเทศด้วยกระบวนการพี่เลี้ยง (Coaching and Mentoring) แบบวัด เจตคติที่มีต่อการนิเทศด้วยกระบวนการพี่เลี้ยง วิเคราะห์ข้อมูลด้วยค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า การพัฒนาต้นแบบครูพี่เลี้ยงของนิสิตฝึกประสบการณ์วิชาชีพครูตามแนวการพัฒนาบทเรียนร่วมกันที่พัฒนาขึ้นมีดังนี้ 1) องค์ประกอบของต้นแบบครูพี่เลี้ยง มีดังต่อไปนี้ 1.1) ด้านความรู้ของครูพี่เลี้ยง ประกอบด้วย การจัดการเรียนรู้ การออกแบบการจัดการเรียนรู้ สื่อการเรียนรู้และนวัตกรรมทางการศึกษาการวัดและการประเมินผลการเรียนรู้ 1.2) ด้านทักษะ การนิเทศด้วยกระบวนการพี่เลี้ยง ประกอบด้วย การให้คำปรึกษาและการสอนงาน การสังเกตและการจดบันทึก 1.3) เจตคติที่มีต่อการนิเทศด้วยกระบวนการพี่เลี้ยง 2) ออกแบบกระบวนการพัฒนาต้นแบบครูพี่เลี้ยง ประกอบด้วยขั้นตอนดังต่อไปนี้ 2.1) กำหนดเป้าหมายการพัฒนาบทเรียนร่วมกันระหว่างผู้วิจัย ครูพี่เลี้ยงกลุ่มเป้าหมายและผู้ทรงคุณวุฒิ 2.2) วางแผนบทเรียนและพัฒนาบทเรียนร่วมกันระหว่างผู้วิจัย ครูพี่เลี้ยงกลุ่มเป้าหมายและผู้ทรงคุณวุฒิ 2.3) การนิเทศด้วยกระบวนการพี่เลี้ยง (Coaching and Mentoring) 2.4) สะท้อนความคิดจากการทดลองใช้บทเรียน 2.5) ปรับปรุงแก้ไขบทเรียน 2.6) แลกเปลี่ยนเรียนรู้พร้อมทั้งนำบทเรียนไปใช้และเผยแพร่เพื่อสร้างเครือข่ายชุมชนแห่งการเรียนรู้ (Professional Learning Community: PLC) โดยเน้นทักษะกระบวนการทำงานร่วมกัน การร่วมมือรวมพลังเพื่อความก้าวหน้าในวิชาชีพครู ผลจากการประเมินสมรรถนะการจัดการเรียนรู้และการนิเทศด้วยกระบวนการพี่เลี้ยงของครูพี่เลี้ยง พบว่า ด้านความรู้ ด้านทักษะการนิเทศด้วยกระบวนการพี่เลี้ยง และเจตคติที่มีต่อการนิเทศด้วยกระบวนการพี่เลี้ยงค่าดัชนีความสอดคล้องรายข้อมีค่าอยู่ระหว่าง 0.67 – 1.00 ซึ่งมีค่าสูงกว่าเกณฑ์ที่กำหนด คำสำคัญ : ต้นแบบครูพี่เลี้ยง การฝึกประสบการณ์วิชาชีพครู กระบวนการพี่เลี้ยง ABSTRACT The objectives of this research are 1) to study the elements of the mentor model for pre-service teacher students in Patumwan Demonstartion School,Srinakharinwirot University. 2) to develop the process of mentor model for pre-service teachers; to compile overall lessons in order to prepare the mentor model for pre-service teacher students having competencies in terms of knowledge and skills as appropriate; to promote teacher professional development; and to create a professional learning community network (Professional Learning Community: PLC).The operations research has been divided into 2 phases: Phase 1- drafting the elements of the mentor model for pre-service teacher students and Phase 2 – developing and designing procedure and process of the mentor model for pre-service teacher students. Research tools used are a pre-service teacher student self-assessment form with competencies in terms of learning - based management and supervision by Coaching and Mentoring process and Attitude Test supervised by Coaching and Mentoring process. The data is analyzed by using Mean, Standard Deviation and Content Analysis. The research results have found out that a development of the mentor model for pre-service teacher students with co-developing common lessons are based on the following factors: 1.1)mentor’s knowledge consisting of learning-based management, designing learning-based management, learning media and educational innovation of learning measurement and evaluation 1.2) supervision skill by Coaching and Mentoring process consisting of coaching and mentoring, observation and record taking. 1.3) attitude towards the mentor model for pre-service teacher students. 2) The development process of the mentor model for pre-service teacher students consists of 2.1) identifying the purposes of co-developing overall lessons among researchers, target groups and experts, 2.2) planning and taking overall lessons among researchers, mentor model target groups and experts, 2.3) supervision by Coaching and Mentoring process, 2.4) reflection from the experiment of overall lessons, 2.5) improving and updating overall lessons, 2.6) exchange learning with applying and publishing overall lessons to create a professional learning community network (Professional Learning Community: PLC) focusing on skills of collaborative working process, cooperation for teacher career advancement. The results of the mentor model learning management and for pre-service teacher student, self-assessment have found out that competencies in terms of knowledge and supervision by Coaching and Mentoring process and Attitude Test to supervised by Coaching and Mentoring process. For Index of Item-Objective Congruence for each item, the range of index score was 0.67 – 1.00 which was higher than the initial criterion. Keyword : The mentor mode,l Practice Teaching, Coaching and Mentoring